PENANAMAN NILAI PANCASILA DALAM MUATAN PPKN SEKOLAH DASAR UNTUK MENGHADAPI ERA GLOBALISASI DIGITAL - Ahmad Syukur; Siti Musyarofah Nur Halimah; Lu’luul Maknun; Santoso; Wawan Shokib Rondli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study emphasizes the importance of instilling Pancasila values ​​through PPKn learning in elementary schools as a provision for students to face challenges in the digital era. Amidst the flood of information and foreign cultural influences, the formation of children's character becomes very important. The results of the literature review show that elementary school is the right time to form values ​​such as divinity, humanity, unity, deliberation, and social justice. The challenges faced include the entry of foreign ideologies, hoaxes, and declining morals. Therefore, Pancasila learning needs to be strengthened in an interesting way and in accordance with the times. In conclusion, Pancasila education at the elementary level is a strategic step to form a generation with character and ready to face the digital era.